Maintenance of Pole Mounted Circuit Breaker as Medium Voltage Network Protection at PT.XYZ: Pemeliharaan Pole Mounted Circuit Breaker Sebagai Proteksi Jaringan Tegangan Menengah di PT. XYZ - Faris, Faisal; Wisaksono, Arief (Universitas Muhammadiyah Sidoarjo, 2024)
The increasing demand for electricity requires PT. XYZ to provide a sufficient, reliable, safe, high-quality, and efficient source of electrical energy. In serving customers, especially those in the Medium Voltage (MV) category, good protective equipment is needed. However, conventional protective equipment often tends to be large, requires ample land space, and installation is time-consuming. This research covers variables such as contact resistance measurement, PMT (Power Circuit Breaker) synchronism testing, and insulation resistance measurement. Using the Research and Development (R&D) method, the results of maintenance on the 20 kV PMT at PMCB KPI P. Sidomulyo, Buduran Subdistrict, revealed that the contact resistance measurement values for phases R, S, and T were below 100 µΩ, indicating good contact resistance. PMT synchronism testing produced time difference values that were within the permissible standard limits. The time difference when opening (open) was 0.7 ms, while when closing (close), it was 1.05 ms. Insulation resistance measurements showed values that met the standards, which were above 20 MΩ. Based on the research results, PMCB KPI P. Sidomulyo, Buduran Subdistrict, can still be considered suitable for use. With good protective equipment and measurements that meet the standards, the use of 20 kV PMT can remain efficient and safe for consumers.